APPLICATION OF WIRELESS SENSOR NETWORK FOR MANUFACTURING AUTOMATIC DUCK EGG HATCHER MACHINE - Ihdalhubbi Maulida ihdal; Windarsyah; Ayu Ahadi Ningrum (Fakultas Teknik Universitas Lambung Mangkurat, 2022)
The main problem with duck workers who want to incubate eggs is that eggs turn two times a day. It causes farmers still use conventional hatching to incubate eggs, usually done manually. This study aims to make an automatic duck-egg incubator using a wireless sensor network. The making of incubator uses a 5-watt incandescent lamp, 5V relay, DHT11, soundsensor, LCD I2C, Wifi ESP8266 01, and a pipe designed to perform egg turning assisted by a servo motor as a driver for the pipe. The average temperature for this automatic incubator sets at 39 – 40 degrees Celcius. The results of this research hatching machine can work as planned. In the first experiment, we should insert four eggs and managed to incubate them, and two eggs managed to come out of the eggshell. In the second experiment, we should insert four eggs and managed to incubate three eggs to come out of the eggshell. So the percentage of success in hatching eggs using an automatic duck egg incubator using this wireless sensor network is in the first experiment as many as 50% or two eggs and in the second experiment as much as 75% or three eggs.